Fuzzy model of a human control operator in a compensatory tracking loop - Shaw, I.S. (International journal of man-machine studies, 1993)
The subject of this work is the characterization of a fuzzy control operator model that can successfully emulate the functioning of a human control operator in a compensatory tracking loop on a real-time basis. After a learning period spent in the proximity of the real human operator being modelled, the model is capable of functioning when physically removed from the site. A systematic fuzzy modelling technique capable of emulating a prototype dynamic system on the basis of its input-output behaviour only is concisely presented and the application of these techniques to a human operator/controller in a tracking loop is illustrated. Experimental results are shown with different driving functions, plant dynamics, and model orders. The fuzzy model can emulate human operators with widely varying tracking abilities.